Implementasi Metode Musyabahah Dalam Pembelajaran Mufradat Bahasa Arab Pada Mahasiswa PBA Universitas Al-Falah Assunniyyah (UAS) Kencong, Jember - Zaeni, Akhmad; Taubah, Miftachul (INAIFAS Press, 2023)
The selection of the musyabahah method used specifically in learning Arabic can be used as an alternative learning method. The primary data sources are the results of interviews and observations, the secondary data sources are the latest book